Digital Transformation of Villages in the Framework of Fiqh Siyasah and Good Governance - Kurniawati, Fifi; Syukur, Iskandar; Nurkholidah, Susi (Jurnal Ilmu Hukum Kyadiren, 2025)
This study explores the implementation of the Smart Village program in the digitalization of administrative services in Bangun Rejo Village, Central Lampung, through the lens of fiqh siyasah and the principles of good governance. The program represents a governmental initiative aimed at enhancing public service delivery through the use of information technology. Employing a descriptive qualitative method, data were collected through observation, interviews, and documentation. The findings reveal that the program encounters several challenges, particularly in technological infrastructure, human resource capacity, and community engagement. Nevertheless, from a fiqh siyasah perspective, the initiative reflects the responsibility of ulil amri (legitimate authority) to promote public welfare. In conclusion, the success of the Smart Village program relies significantly on strengthening digital literacy, fostering multi-sector collaboration, and implementing governance practices rooted in Islamic ethics that emphasize participatory and responsive principles.